2019
DOI: 10.15386/mpr-1261
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular obstruction in acute myocardial infarction: an old and unsolved mystery

Abstract: In the setting of acute myocardial infarction, flow restoration in the culprit epicardial coronary artery is not synonymous with efficient reperfusion. Microvascular obstruction occurs in 50% of cases and represents a predictor of a long-term unfavorable outcome. Its prevalence has remained constant in recent years despite various treatment attempts. However, the success of targeted therapies could be mainly a problem of timing. Recent data bring evidence with regard to the role of pre-procedural distal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…This result reveals that the coronary microcirculation status in patients with HFmrEF is comparable to that in patients with HFrEF, but poorer than that in patients with LVEF > 50%. The presence of CMD after STEMI predicts adverse prognoses such as rehospitalization, HF, and mortality [ 23 , 24 ]. It is also a powerful predictor of LV adverse remodeling [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result reveals that the coronary microcirculation status in patients with HFmrEF is comparable to that in patients with HFrEF, but poorer than that in patients with LVEF > 50%. The presence of CMD after STEMI predicts adverse prognoses such as rehospitalization, HF, and mortality [ 23 , 24 ]. It is also a powerful predictor of LV adverse remodeling [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, regardless of intervention, no-reflow, and the coronary slow-flow phenomenon are common and can occur after PPCI [3][4][5][6][7][13][14][15][16]. Indeed, in severe instances, this is termed thromboembolic syndrome [13][14][15][16][17][18]. Studies found that GPI administration improved TIMI flow, ameliorated myocardial reperfusion injury, prevented myocardial ischemia, reduced MACEs, and improved prognosis [5,11,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Antiplatelet therapy is also a cornerstone of AMI treatment. Yet, regardless of intervention, no-reflow, and the coronary slow-flow phenomenon are common and can occur after PPCI [3][4][5][6][7][13][14][15][16]. Indeed, in severe instances, this is termed thromboembolic syndrome [13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, regardless of intervention, no-re ow is common and can occur after PPCI [3][4][5][6][7]. Indeed, in severe instances this is termed thromboembolic syndrome [12][13][14][15][16][17]. Studies found that GPI administration improved TIMI ow, ameliorated myocardial reperfusion injury, prevented myocardial ischemia, reduced MACEs, and improved prognosis [5,[18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%